PENGARUH SUBTITUSI TEPUNG KACANG HIJAU TERHADAP DAYA TERIMA DAN KADAR PROTEIN PADA KASTENGEL SEBAGAI SALAH SATU KUDAPAN ALTERNATIF STUNTING - Fidatul Jamila; Fitria Fitria; Fitriana Nugraheni; Tika Fatihatul Khoir (LPPM Institut Pendidikan Nusantara Global, 2023)
Stunting can be controlled by eating foods that have a high protein content. One of the foods high in protein content is green beans. Protein can assist in the repair of damaged growth cells and support optimal nutritional status in children. Therefore, green beans need to be further developed so that they are useful for humans as a mixture or addition to food, one of which is kastengel. The addition of green beans is expected to increase the nutritional value, especially protein in kastengel. This study aims to determine the organoleptic quality and protein content of mung bean kastengel. The method used was experimental with Completely Randomized (CRD) 3 treatments and 2 replications. This research was conducted with objective and subjective tests. The objective test was carried out by laboratory testing of protein content using the Kjehdahl test. The subjective test was carried out by organoleptic test with 30 panelists in the category of panelists not choosing. The analytical technique used was Kruskal Wallis statistical analysis and continued One Way Anova to determine the effect of acceptability and protein content between treatments. This study shows that the most preferred organoleptic is the formulation with a ratio of wheat flour and mung bean flour as much as 25%: 75% with a reassessment of color, taste, aroma, texture, which is 3.65 (very like). The results of the Kruskal Wallis test on color, aroma, taste, and texture were (p < 0.05). One Way Anova test results on protein test results obtained (p < 0.05). There is an effect of treatment of each sample on the indicators of color, aroma, taste, and texture and there is also an effect of treatment of each sample on the results of the protein test.